JOURNAL OF GOVERNMENT & POLITICS : Mobilizing Resources but Still Mining for Opportunities? : Indigenous Peoples, their Land and the Philippine State - Prince Aian G Villanueva, Anfernee P Ruanto (FISIPOL UMY, 2016)
The Kalipunan ng mga Katutubong Mamamayan ng Pilipinas (KAMP) or the National Aliance of Indigenous peoples Orgaization in the Philippines is almost in their 30 years of existence and yet like in most cases of Indigenous people issues.